You are a bad ass : how to stop doubting your greatness and start living an awesome life - Sincero, Jen, 1965- (Philadelphia : Running Press, 2013)
Offers a blunt and irreverent guide to achieving the money, relationships, career, and happiness that one desires through recognizing and doing away with self-sabotaging beliefs and behaviors
Introduction -- How you got this way. My subconscious made me do it -- The G-word -- Present as a pigeon -- The big snooze -- Self-perception is a zoo -- How to embrace your inner badass. Love the one you is -- I know you are but what am I? -- What are you doing here? -- Loincloth man -- How to tap into the motherlode. Meditation 101 -- Your brain is your bitch -- Lead with your crotch -- Give and let give -- Gratitude: the gateway drug to awesomeness -- Forgive or fester -- Loosen your bone, Wilma -- How to get over your B.S. already. It's so easy once you figure out it isn't hard -- Procrastination, perfection, and a Polish beer garden -- The drama of overwhelm -- Fear is for suckers -- Millions of mirrors -- The sweet life -- How to kick some ass. The almighty decision -- Money, your new best friend -- Remember to surrender -- Doing vs. spewing -- Beam me up, Scotty
Includes bibliographical references (pages 245-252)
Keywords: Self-help techniques; Self-actualization (Psychology)